2009
DOI: 10.1007/s00221-009-1802-9
|View full text |Cite
|
Sign up to set email alerts
|

Location-specific modulations of plantar cutaneous reflexes in human (peroneus longus muscle) are dependent on co-activation of ankle muscles

Abstract: Cutaneous reflexes induced in lower leg muscles by non-noxious electrical stimulation to the foot sole are strongly modified depending on the stimulated location. Little is known, however, about the functional importance of this location-specificity. We examined modulation of cutaneous reflexes in the peroneus longus muscle during co-activation of the peroneus longus (PL), soleus, and tibialis anterior muscles in ten healthy volunteers. We successfully recorded 121 intramuscular single motor units (MU) of cuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
2
14
0
2
Order By: Relevance
“…That is, the amplitude of the ELR was significantly reduced when subjects performed ARM alone and LEG alone compared to ARM&LEG movement. This general feature of task dependency is in line with many previous reports obtained from individual nerve stimulation [2], [11], [12], [14], [20], [23], [25], [32], [34][37]. An extension to this literature found here is that there were no significant differences between reflexes during ARM&LEG movement and mathematical summation of both separate tasks (ARM alone or LEG alone).…”
Section: Discussionsupporting
confidence: 93%
“…That is, the amplitude of the ELR was significantly reduced when subjects performed ARM alone and LEG alone compared to ARM&LEG movement. This general feature of task dependency is in line with many previous reports obtained from individual nerve stimulation [2], [11], [12], [14], [20], [23], [25], [32], [34][37]. An extension to this literature found here is that there were no significant differences between reflexes during ARM&LEG movement and mathematical summation of both separate tasks (ARM alone or LEG alone).…”
Section: Discussionsupporting
confidence: 93%
“…While non-noxious cutaneous reflexes have been studied for the three main nerve trunks innervating the dorsal and plantar foot, only recently have attempts to isolate specific tactile effects from regions of the foot sole been made [13,14]. These studies were restricted to sitting and standing conditions, and limited to forefoot medial, forefoot lateral, and heel stimulation but clearly showed that cutaneous reflexes evoked by stimulation of discrete foot sole regions produced topographical organized reflexes in human ankle muscles [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These studies were restricted to sitting and standing conditions, and limited to forefoot medial, forefoot lateral, and heel stimulation but clearly showed that cutaneous reflexes evoked by stimulation of discrete foot sole regions produced topographical organized reflexes in human ankle muscles [13,14]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intralimb cutaneous reflexes have been demonstrated to possess task dependency (phasic locomotor vs. tonic maintained activity), intensity dependency (noxious vs. non-noxious stimulation), load dependency, phase dependency (swing vs. stance), and laterality dependency (ipsilateral vs. contralateral effects) [6][7][8] . The amplitude of cutaneous reflexes in both arm and leg muscles strongly depends on the location of the skin in which the stimulation was delivered (location specificity) [31][32][33] . These previous studies indicate that cutaneous reflexes are of functional importance for a variety of rhythmic movements for on-going activity in response to tactile sensation.…”
Section: Neurophysiological Bases Of Reflex Responses Arising From Cumentioning
confidence: 99%